2021
DOI: 10.1007/s12011-021-02958-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Zinc Microelement in Aquaculture: a Review

Abstract: Trace elements are required in optimum regimes for improving the productivity and wellbeing of aquatic animals. Zinc is one of the main microelements involved in several functions in the animal's body. Zinc potentiates the metabolism function, synthesis of essential enzymes, and the formation of hormones associated with growth, reproduction, immunity, and antioxidative roles in aquatic animals. Several sources of zinc are regularly applied in aquaculture, including inorganic, organic, and nanoparticles. Many s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Sallam et al [ 85 ] found that the dietary supplementation of zinc–methionine at 30 ppm significantly improved catalase, superoxide dismutase, glutathione peroxidase, and lysozyme activities in marbled spinefoot rabbitfish ( Siganus rivulatus ). Zinc shows the most significant benefits for the immune response as a cofactor of superoxide dismutase, and this antioxidative enzyme is essential in the defense against radical reactions and in decreasing superoxide oxygen species levels in aquatic animals [ 86 , 87 , 88 ], because optimal zinc supplementation in diets tends to increase the level of superoxide dismutase. The major function of dietary chromium is to enhance insulin efficiency by promoting blood glucose uptake in animal metabolism [ 89 ] and improving glucose utilization [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sallam et al [ 85 ] found that the dietary supplementation of zinc–methionine at 30 ppm significantly improved catalase, superoxide dismutase, glutathione peroxidase, and lysozyme activities in marbled spinefoot rabbitfish ( Siganus rivulatus ). Zinc shows the most significant benefits for the immune response as a cofactor of superoxide dismutase, and this antioxidative enzyme is essential in the defense against radical reactions and in decreasing superoxide oxygen species levels in aquatic animals [ 86 , 87 , 88 ], because optimal zinc supplementation in diets tends to increase the level of superoxide dismutase. The major function of dietary chromium is to enhance insulin efficiency by promoting blood glucose uptake in animal metabolism [ 89 ] and improving glucose utilization [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zn is a trace element in the biological body second only to iron, widely distributed in various tissues and organs, with catalytic, structural and regulatory functions. Previous studies have shown that Zn is involved in regulating growth and development, oxidative stress and immune defense of various aquaculture animals, including sh and crustaceans (Dawood et al, 2022;Jiang et al, 2016). However, there has been no report for Apostichopus japonicus.…”
Section: Discussionmentioning
confidence: 99%
“…Zn has a catalytic role for numerous enzymes, aids intra and extra cellular metabolic functions as well as formation of hormones with diverse roles (i.e., growth, reproduction, immunity, etc.) ( Dawood et al, 2021 ; Lall, 2022 ). Zn supplementation has a positive effect on aquatic animal’s performance, immunity, antioxidant status as well as feed utilization and digestibility ( Dawood et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…( Dawood et al, 2021 ; Lall, 2022 ). Zn supplementation has a positive effect on aquatic animal’s performance, immunity, antioxidant status as well as feed utilization and digestibility ( Dawood et al, 2021 ). Fe and Zn, among other components, function as co-factors or coenzyme precursors for essential long chain n-3 polyunsaturated fatty acid (LC n –3 PUFA) biosynthesis ( Lewis et al, 2013 ) and play also role in the bioconversion of alpha-linolenic acid (ALA) to eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) in salmonids ( Mahfouz et al, 1989 ; Eder and Kirchgessner, 1994 ; Stangl and Kirchgessner, 1998 ; Zhou et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%